Kajian kerentanan dan kapasitas terhadap ancaman Bencana Tsunami di Kampung Wamesa, Distrik Manokwari Selatan, Kabupaten Manokwari, Provinsi Papua Barat - Nur R. Hastuti; Ishak Semuel Erari; David Victor Mamengko; Linda Ernawati Lindongi; Syukur Karamang (Program Pascasarjana Universitas Papua, 2023)
This study determined the management of disaster risk reduction in Wamesa Village, South Manokwari District, West Papua Province, and evaluated the level of vulnerability, capacity, and risk of the tsunami catastrophe threat. This research is a quantitative and qualitative research that uses analytical descriptive methods that describe the context of vulnerability and capacity in the research location. The primary data were collected through interviews with community development cadres of Wamesa village as well as documentation (mapping) of social, economic, physical and environmental data at the research location referring to the technical research guidelines for tsunami disaster risk study. Secondary data to see potential threats as well as vulnerability and capacity level assessments were obtained from the relevant agencies. The results found that the level of vulnerability and capacity of the Wamesa village community to the tsunami disaster was categorized as high with a vulnerability and capacity index values were 2.21 and 2.54, respectively. Wamesa village, in general, is at intermediate risk of a tsunami disaster, with a total of 0.92 ha of the hamlet's land area being at low risk, 46.13 ha being at moderate risk, and 2.91 ha being at high risk. The management of disaster risk reduction in Wamesa village needs to be strengthened by integrating risk assessment and disaster mitigation activities into village planning and budgeting so it can be sustainable and contributes to reducing vulnerability and increasing the capacity of the Wamesa village against the threat of a tsunami disaster.